LAPORAN KEUANGAN INTERIM BAGI SUSTAINABILITY RUMAH TANGGA SAKINAH MAWADDAH WARAHMAH - Tenriwaru Tenriwaru; Fatma Azzahra; Fifi Nurafifah Ibrahim (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to determine the interim financial statements to form sustainability in the sakinah mawaddah warahmah household. The method used in this study is a qualitative method with a phenomenological research approach. This research uses primary data in collecting data by interview and documentation study. There were five informants in this study who were in the city of Makassar which was the place of research. All informants are housewives who have a major role in managing household finances. The results of this study indicate that the role of household financial accounting in the three categories studied are; Planning in which all informants plan with the same capital, namely by planning household needs every month at the beginning of the month by estimating how much costs will be incurred during the next month. The recording made by the informant is not a recording of every transaction. Decision-making carried out by informants always involves the head of the household if the decision-making is related to important matters or large transactions, but in the recording category it has not been applied properly by housewives and some informants did not record. The important role of accounting and the benefits of applying accounting in married life is useful for knowing the distribution of income and expenses in meeting household needs, making household finances detailed and well organized. Used as an accountability in the financial welfare of a sakinah mawaddah warahmah household.